Pengaruh Peran Guru Pendidikan Agama Islam (PAI) terhadap Peningkatan Literasi Baca Tulis Al-Qur’an (BTQ) pada Siswa Sekolah Dasar (SD) Kelas VI di Kecamatan Balongan Kabupaten Indramayu - Nurul Inayah; Siti Mulkiyah; Fitriah Fitriah; Muhammad Aulia Taufiqi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to determine the extent of the influence of Islamic Education (PAI) teachers' roles in improving Qur’anic Literacy (BTQ) among sixth-grade elementary school students in Balongan District, Indramayu Regency. The research employs a quantitative approach using a correlational method to examine the relationship between the two variables in a more measurable way. A total of 200 students were selected as the research sample using a probability sampling technique to ensure fair representation of the population. Data collection was carried out through two main instruments: a questionnaire to measure the perceived role of PAI teachers and a test to assess students’ BTQ skills. The collected data were analyzed with the help of SPSS version 26 using the Pearson Product Moment correlation technique. The analysis results showed a correlation value of 0.535 with a significance level of 0.05, indicating a strong and significant relationship between the role of PAI teachers and students’ BTQ literacy. Therefore, it can be concluded that PAI teachers have a positive influence in enhancing students’ ability to read and write the Qur’an.